2021
DOI: 10.1111/jfr3.12770
|View full text |Cite|
|
Sign up to set email alerts
|

Country‐wide flood exposure analysis using Sentinel‐1 synthetic aperture radar data: Case study of 2019 Iran flood

Abstract: Extreme precipitation and flooding often lead to human and economic losses. However, the high-resolution nationwide flooding exposure data are scarce.Availability of all-weather space-borne SAR satellite data can potentially improve the ability to generate high-resolution flood map extent and exposure globally. In Iran, flooding is a major concern, given the socioeconomic vulnerabilities and increased likelihood of climate extremes. Iran experienced extreme flooding during January to March 2019, attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…These characteristics cause the region to have most land usable for cropping and agriculture based on the suitability index, of which one of the parameters is precipitation (Mesgaran et al ., 2016). However, followed by Caspian Sea coastal regions, extreme precipitation events both in magnitude and frequency are highest in western Zagros (Alijani et al ., 2008; Sherpa and Shirzaei, 2022) which has a negative impact on these agricultural lands. In winter and spring, the region is frequently affected by merged Mediterranean and Sudanese systems, which produce heavy rainfall exceeding 100 mm·hr −1 (Ghasemifar et al ., 2017; Kiani et al ., 2020).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…These characteristics cause the region to have most land usable for cropping and agriculture based on the suitability index, of which one of the parameters is precipitation (Mesgaran et al ., 2016). However, followed by Caspian Sea coastal regions, extreme precipitation events both in magnitude and frequency are highest in western Zagros (Alijani et al ., 2008; Sherpa and Shirzaei, 2022) which has a negative impact on these agricultural lands. In winter and spring, the region is frequently affected by merged Mediterranean and Sudanese systems, which produce heavy rainfall exceeding 100 mm·hr −1 (Ghasemifar et al ., 2017; Kiani et al ., 2020).…”
Section: Study Areamentioning
confidence: 99%
“…Some recent studies (e.g., Modarres et al ., 2016; Alavinia and Zarei, 2020) showed that although the overall trend of precipitation has decreased, flood magnitude has increased in western and northwestern Iran. This trend is highly correlated with changes in Mediterranean and Sudanese cyclone intensity (Khoshakhlagh et al ., 2008; Sabziparvar et al ., 2010; Heydari and Khoshakhlag, 2015; Bayat et al ., 2017; Kiani et al ., 2020; Rezaei et al ., 2021; Sherpa and Shirzaei, 2022).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1e depicts the meteorological dynamics in relation to the availability periods of the global data products used in this study. It shows that for Iran, the analyzed period of vegetation dynamics (covered by MODIS data) coincides with a pronounced severe dry period between 1999 and 2001 forming the onset of a 20-year warm and dry period (compared to 1980-2000) ending with a very wet year in 2019, which was characterized by extensive flooding [61][62][63][64] . Thus, the available MODIS based vegetation growth observations almost exclusively comprise a continuous warm and dry period that started in the year 1999.…”
mentioning
confidence: 99%